Matrix metalloproteinases as therapeutic targets in breast cancer - Kwon, Mi Jeong (Frontiers in Oncology, 2023)
Matrix metalloproteinases (MMPs) are the most prominent proteinases involved in tumorigenesis. They were initially recognized to promote tumor progression by remodeling the extracellular matrix through their proteolytic activity. However, accumulating evidence has revealed that some MMPs have protective roles in cancer progression, and the same MMP can exert opposing roles depending on the cell type in which it is expressed or the stage of cancer. Moreover, studies have shown that MMPs are involved in cancer progression through their roles in other biological processes such as cell signaling and immune regulation, independent of their catalytic activity. Despite the prognostic significance of tumoral or stromal expression of MMPs in breast cancer, their roles and molecular mechanisms in breast cancer progression remain unclear. As the failures of early clinical trials with broad-spectrum MMP inhibitors were mainly due to a lack of drug specificity, substantial efforts have been made to develop highly selective MMP inhibitors. Some recently developed MMP inhibitory monoclonal antibodies demonstrated promising anti-tumor effects in preclinical models of breast cancer. Importantly, anti-tumor effects of these antibodies were associated with the modulation of tumor immune microenvironment, suggesting that the use of MMP inhibitors in combination with immunotherapy can improve the efficacy of immunotherapy in HER2-positive or triple-negative breast cancer. In this review, the current understanding of the roles of tumoral or stromal MMPs in breast cancer is summarized, and recent advances in the development of highly selective MMP inhibitors are discussed.